2023
DOI: 10.1101/2023.05.31.541819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generating human neural diversity with a multiplexed morphogen screen in organoids

Abstract: Morphogens choreograph the generation of remarkable cellular diversity in the developing nervous system. Differentiation of stem cells toward particular neural cell fates in vitro often relies upon combinatorial modulation of these signaling pathways. However, the lack of a systematic approach to understanding morphogen-directed differentiation has precluded the generation of many neural cell populations, and the general principles of regional specification remain incomplete. Here, we developed an arrayed scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…As our approach for quantifying the preservation of co-expression is derived from a genome-wide co-expression network of primary neural tissue, we can also putatively assess preserved co-expression of more specific cell-type markers. We investigate preserved co-expression of more specific cell-type markers by utilizing marker genes derived from a morphogen screen in neural organoids that reported the production of extensive neural cell-type diversity 48 . As examples of protocol specific trends, we show the dorsal patterned forebrain organoid preserves co-expression of telencephalic excitatory neuron markers over markers for mib-brain and thalamic excitatory neurons as well as dopaminergic mid-brain neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As our approach for quantifying the preservation of co-expression is derived from a genome-wide co-expression network of primary neural tissue, we can also putatively assess preserved co-expression of more specific cell-type markers. We investigate preserved co-expression of more specific cell-type markers by utilizing marker genes derived from a morphogen screen in neural organoids that reported the production of extensive neural cell-type diversity 48 . As examples of protocol specific trends, we show the dorsal patterned forebrain organoid preserves co-expression of telencephalic excitatory neuron markers over markers for mib-brain and thalamic excitatory neurons as well as dopaminergic mid-brain neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To define markers for finer resolution cell-types, we utilize the differential expression (DE) statistics computed from a study that performed a morphogen screen in neural organoids and reported extensive neural cell-type diversity 48 . For each cell-type, we rank genes by their adjusted DE p-value and take the top 10 genes per cell-type to compute preserved co-expression scores.…”
Section: Methodsmentioning
confidence: 99%
“…The integrated HNOCA, as well as the analytical pipeline we established to compare to the primary reference atlas in terms of cell type composition and transcriptomic fidelity, provide a framework to query novel neural organoid scRNA-seq data sets not included in the HNOCA. To showcase this application, we retrieved the scRNA-seq data of a recently published multiplexed neural organoid morphogen screen 13 , and projected it to the same latent spaces as the HNOCA and the primary reference 12 , respectively, using scArches (Fig. 4a, Extended Data Fig.…”
Section: The Hnoca Facilitates Evaluation Of New Neural Organoid Prot...mentioning
confidence: 99%
“…We further estimate transcriptomic fidelity of neurons in neural organoids and identify cell stress as a universal factor distinguishing metabolic states of in vitro neurons from primary neurons. Finally, we map the data of a recent neural organoid morphogen screen 13 to the integrated atlas to assess regional specificity, and generation of novel states. Together, our work provides a rich atlas resource and a new framework to assess the fidelity of neural organoids, characterize perturbed and diseased states and streamline protocol development in the future.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation